ARTIFICIAL AND NATURAL INTELLIGENCE IN ANTHROPOGENIC EDUCATIONAL ENVIRONMENTS - Sergey F. Sergeev (Открытое образование (Москва), 2016)
In the present article we show the link between both artificial and natural intelligence and the system’s complexity during the life-cycle. Autopoetic’s type of living systems determines the differences between natural and artificial intelligence; artificial environments have an influence to the intelligence abilities development. We present the «diffusion intellect» concept where the diffusion intellect is considered as a synergistic unity of natural and artificial intellect in organized environments.